(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background- When a patient receives the vaccine, their immune system is triggered to produce antibodies, preparing them to battle any coronavirus infection Objectives- To Assess the post Vaccination symptoms of Covaxine in adult population (more than 18 Year). To evaluate the quality of life after completion of both the doses as per WHOQOL Questionnaire. Methods- A Phase III, Randomized, Open blind, A Pilot study to evaluate the safety of COVAXIN in Post vaccination of adults s <60 Years of group study Patients who fulfill protocol specific Inclusion/Exclusion criteria will be included in the study after informed consent has been obtained. The design and focus of the study are dependent on the current COVID-19 pandemic, requiring identification of participant candidates at high risk of SARS-CoV-2 infection. The Sponsor may adjust the size of the study or duration of follow-up based on the blinded review of the total number of cases of COVID-19 accrued during the study, in addition to estimated percentages of study participants with immunologic evidence of SARS-CoV-2 infection at baseline. A total of 100 subjects with equal randomization between treatment groups will be targeted for the current study. Results- Analysis of 1st dose showed a total no. of 100 subjects completed study. Out of which, 12% subject having Fever in 5% are female & 7% are Male. 88% not having Fever, in 23% are female & 65% are male subject. Out of which, 2% subject having Cough in 1% are female &1% are male and 98% not having Cough in 27 % are female & 71% are male, 1% subject having Breathlessness in 1% are male and 99% not having Breathlessness in 28 % are female & 71 % are male. 48% suggest good quality of life post vaccination. 38% had negative feelings very often like depression, anxiety post vaccination Conclusion- We found that most of the participants reported fever, pain at the site of the injection, body ache, and headache, and they are more common in those after the second dose of the vaccines. A follow-up study on population is warranted to evaluate the safety of the vaccine on the control and prevention of SARS-CoV-2 infection as well as the long-term side effects.